Explorers of the twenty-first century? A systematic literature review of the scholarship on international entrepreneurs from developed economies - Maximilian Scheu; Andreas Kuckertz (International Entrepreneurship and Management Journal, 2022)
Throughout history, expeditionists and explorers have discovered foreign countries and new worlds, markedly influencing the lives of succeeding generations. However, as multinational enterprises have come to drive globalisation, the existence of entrepreneurial individuals without the resources of large corporations is a relatively recent phenomenon. Although research on migrant entrepreneurs demonstrates the positive impact that foreign entrepreneurial activity can have on job creation and innovation, a clear perspective on entrepreneurs from developed economies venturing abroad is lacking. The study aggregates evidence from 33 articles to establish a unifying framework that describes the foreign entrepreneurial process originating in developed economies. The framework proposes categorising foreign entrepreneurial activity according to social and economic dimensions and introduces four archetypes of foreign entrepreneurs, helping us understand the dynamics of the institutional context and the motivations for venturing into foreign environments. Finally, the study discusses the implications for foreign entrepreneurs and considers future research avenues.
Keywords: 650; International entrepreneurship; Developed countries; Foreign entrepreneurship; Literature review; Migration